An Investigation into Linguistic Features of Transitive Verbs in Verbal Processes of the Novel Series Fifty Shades by El James and its Vietnamese Translational Version 50 Sắc Thái by Van Khanh, Dang Ngoc - Phan Thị Hoàng Oanh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Communication is the process by which we share and understand information. From the past until now, it is believed that using the right words in communication shows the talent and dignity of the speaker. Therefore, there is an old saying “True gold is to be tested with coal and fire. Good bells by how they reverberate. Good people by how they verbalize.” In other words, the importance of selection of the appropriate words to match with specific speakers in a certain communication context cannot be denied. The study attempts to investigate the linguistic patterns of the verbal processes in an English novel and its Vietnamese translated version. Differences between transitive verbs in terms of syntactic features and semantic features in verbal processes in both novels are explored as well.